2008
DOI: 10.1016/j.bmcl.2008.03.037
|View full text |Cite
|
Sign up to set email alerts
|

4′-Methyl-4,5′-bithiazole-based correctors of defective ΔF508-CFTR cellular processing

Abstract: The synthesis and Delta F508-CFTR corrector activity of a 148-member methylbithiazole-based library are reported. Synthetic routes were devised and optimized to generate methylbithiazole analogs in four steps. Corrector potency and efficacy were assayed using epithelial cells expressing human Delta F508-CFTR. These structure-activity data establish that the bithiazole substructure plays a critical function; eight novel methylbithiazole correctors were identified with low micromolar potencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 13 publications
0
49
0
Order By: Relevance
“…Our previous work, 57 especially that with tethered bithiazoles such as 1a , provides circumstantial evidence in support of a “U-shaped” bioactive conformation (Figure 2), rigidified in part by S•••lone pair interactions. 6,25 The overall lowest energy conformer found for each compound, along with the lowest energy U-shaped conformer (both in water) are shown in Table 2 (see Supporting Information for additional details, including interatomic distances).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous work, 57 especially that with tethered bithiazoles such as 1a , provides circumstantial evidence in support of a “U-shaped” bioactive conformation (Figure 2), rigidified in part by S•••lone pair interactions. 6,25 The overall lowest energy conformer found for each compound, along with the lowest energy U-shaped conformer (both in water) are shown in Table 2 (see Supporting Information for additional details, including interatomic distances).…”
mentioning
confidence: 85%
“…4 The recent work of Yoo et al indicates that bithiazole 1 , a 4-(thiazol-5-yl)thiazole derivative, has significant corrector action on the mutant ΔF508-CFTR. 5 A bithiazole-focused structure-activity-relationship study by Yu et al showed that an s-cis coplanar conformation of the bithiazole, a peripheral pivolyl group, and a substituted aniline moiety are crucial structural features in eliciting ΔF508-CFTR corrector activity with the bithiazole chemo type. 6 Indeed, the s-cis coplanar conformation, as exemplified by bithiazole 1a wherein the two thiazole rings are constrained by an alkyl chain, is required for corrector activity.…”
mentioning
confidence: 99%
“…5,8,12 Cells were grown at 37 °C (95% air/5% CO 2 ) for 24 h and then incubated for 16–20 h with 50 μL of medium containing the test compound. At the time of the assay, cells were washed with PBS and then incubated with PBS containing forskolin (20 μM) and genistein (50 μM) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…5,8,12 Correctors at various concentrations (and negative/positive controls) were added to each well and incubated for 18–24 h. ΔF508–CFTR-facilitated iodide influx was determined from the kinetics of YFP-H148Q/I152L quenching in response to iodide addition in cells treated with a cAMP agonist forskolin and the potentiator genistein.…”
Section: δF508–cftr Correction Bioassaymentioning
confidence: 99%
“…(1); [66] potentiator SF-03 (2); [33] potentiator PG-01 (3); [33] potentiator VRT-532 (4); [34] potentiator NSOO4 (5); [67] corrector compound 4 a (6); [24] potentiator dF508act-02 (7); [32] corrector (8); [24] potentiator (9); [68] potentiator (10); [68] corrector VRT-640 (11); potentiator (12); [41,68] corrector VRT-325 (13); [34,69] corrector compound 5 a (14); [24] corrector compound 5 c (15); [24] potentiator genistein (16); [67] corrector KM11060 (17); [39] corrector vertex patent (18); corrector genzyme compound 48 (19); [70] corrector KM11057 (20); [39] corrector dynasore (21); [71] corrector compound 4 c (22); [24] corrector compound 2 i (23); [24] corrector compound 2 b (24); [24] corrector compound 4 d (25); [24] corrector compound 3 d (26); [24] corrector compound 15 Jf (27). [72] 248 www.chemmedchem.org veals that, to date, all available therapies are focused on treating the symptoms associated with CF rather than on curing the disease. While current medications have been extremely successful in increasing the lifespan and improving the quality of life of CF patients, there is a clear need for the development of new treatments that will target the underlying molecular defects that cause CF.…”
Section: Ligand-related Informationmentioning
confidence: 99%